Analysis of Students' Mathematical Literacy in Curved-Surface Solids Based on Learning Motivation - Abdul Hakim Maruf Ma'ruf; Siti Umi Rokhani; Yayah Amalia; Natasya Nazwa; Samson Worku Teshome (HAMKA INSIGHT, 2026)
Abstract Purpose: This study aims to describe students' mathematical literacy in solving problems involving curved-surface solids according to low, moderate, and high levels of learning motivation. Method: A descriptive qualitative design was employed. The participants were 10 ninth-grade students at MTs Miftahul Huda. Data were collected using three contextual mathematical literacy tasks, a 10-item learning motivation questionnaire, and follow-up interviews. Three focal participants representing low, moderate, and high learning motivation were selected for in-depth analysis. Findings: Students with low learning motivation met few mathematical literacy indicators and had trouble identifying relevant information, constructing mathematical models, applying appropriate procedures, and interpreting results. Students with moderate motivation met several indicators but did not consistently present systematic solution processes or relate their results to the problem context. Practical implications: Mathematics teachers should combine contextual problem-solving activities with strategies that strengthen persistence, confidence, and independent learning. Students with low learning motivation require structured scaffolding, feedback, and sustained encouragement, while students with higher motivation should receive opportunities for independent exploration and reflective problem solving. Originality/value: This study provides a qualitative account of how mathematical literacy varies across three levels of learning motivation in the specific context of curved-surface solids. It integrates written solution analysis and interview evidence to explain students' performance in the PISA processes of formulating, employing, and interpreting mathematics.